Pola Kepemimpinan Dewan Pastoral Paroki Hati Kudus Yesus Mangkupalas - Maria Regina Kaha; Zakeus Daeng Lio (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2017)
The study used qualitative and phenomenological analyses to find the themes and categories of the informant answers. The results of this study show that the categories of the leadership pattern emerged are as the following: the leadership function is serving function, the leadership traits are organic, the leadership style is cooperative, the leadership orientation is the shared of goal, and the actors’ leadership tend to be positive. The general pattern of leadership run by the Pastoral Council at the Parish of Hati Kudus Yesus Mangkupalas is known as the pattern of participative-cooperative leadership. The leadership pattern of participative-cooperative is a suitable pattern offered for the leadership in church community, by putting forward fraternal closeness, shared and mutual negotiation, and encourage self-reliance, so that a common purpose could be reached democratically.